Prosocial video game as an intimate partner violence prevention tool among youth: A randomised controlled trial. (April 2019) - Boduszek, Daniel; Debowska, Agata; Jones, Adele D.; Ma, Minhua; Smith, David; Willmott, Dominic; Trotman Jemmott, Ena; Da Breo, Hazel; Kirkman, Gillian
Abstract: Evidence demonstrates that exposure to prosocial video games can increase players' prosocial behaviour, prosocial thoughts, and empathic responses. Prosocial gaming has also been used to reduce gender-based violence among young people, but the use of video games to this end as well as evaluations of their effectiveness are rare. The objective of this study was to assess the effectiveness of a context-specific, prosocial video game, Jesse, in increasing affective and cognitive responsiveness (empathy) towards victims of intimate partner violence (IPV) among children and adolescents ( N  = 172, age range 9–17 years, M  = 12.27, SD  = 2.26). A randomised controlled trial was conducted in seven schools in Barbados. Participants were randomly assigned to an experimental (prosocial video game) or control (standard school curriculum) condition. Experimental and control group enrolled 86 participants each. Girls and boys in the experimental condition, but not their counterparts in the control condition, recorded a significant increase in affective responsiveness after intervention. This change was sustained one week after game exposure. No significant effects were recorded for cognitive responsiveness. Findings suggest that Jesse is a promising new IPV prevention tool among girls and boys, which can be used in educational settings. Highlights: The aim was to assess the effectiveness of a context-specific, prosocial video game – Jesse. The sample (N = 172) consisted of boys and girls randomly assigned to experimental and control group. The outcome measure consisted of affective and cognitive responsiveness (empathy) towards victims of IPV. A randomised controlled trial revealed a significant increase in affective responsiveness after exposure to game.